The Role of Social Media in Shaping the Behavior of Muslim Generation Z Voters in General Elections - Shafrina, Alifya Nur; Hidayaturrahman, Mohammad; Ubaid, Ahmad Hasan; Sinaga, Astriana Baiti; Elazhari, Elazhari (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
Generation Z voters are easily influenced by exposure to money politics and hoaxes during the general election. This study was conducted to reveal the role of social media in shaping the political behavior of Muslim Generation Z voters in the 2024 general election. This article is the result of qualitative research that specifically describes the behavior of Muslim Generation Z voters. Data collection was carried out using two techniques. First, questionnaires were distributed to 133 respondents, Muslim Generation Z voters consisting of college students and high school students. Second, in-depth interviews with 11 informants comprised of college students and students. The data analysis used in this study uses content analysis in the form of respondents' and informants' answers, which have been collected through questionnaires and in-depth interviews. The results of the study show that Muslim Generation Z voters are familiar with social media such as Instagram, YouTube, TikTok, Facebook, and WhatsApp. These social media are used by Muslim Generation Z voters to access political information. Furthermore, political information on social media plays a role in shaping the behavior of Muslim Generation Z voters in various forms, starting from just being voters, implementing committees, and election supervisors. This study contributes to the theory of voter behavior, shaped not only by sociological, economic, and psychological factors but also by communication factors, especially on social media.